Ethical penalties: A study of possible situational and individual factors to explain less severe punishments to accountants - Lima, Jose Ricarte de; Lima, Aparecida de Fátima Alves; Lima, Ederaldo José Pereira (Seven Editora, 2023)
The objective of this study was to verify whether the factors age and professional experience of counselors who propose punishments explain the application of less severe ethical penalties to accountants. To this end, we analyzed 390 lawsuits filed against professional accountants with active records in the Regional Accounting Council of the State of Mato Grosso, which became final in the period from 2014 to 2018. The study had a probabilistic approach and thus, for the econometric examination, logistic regression was used. The results show that on average, reporting counselors are 58 years old and, on average, 27 years old, have professional experience. In this sense, the older the directors, the less likely they are to apply a warning for ethical infractions and that, more experienced advisors are more likely to punish the offending accountants with warning, that is, a less severe penalty. Descriptive statistics showed that reserved warning, which is considered less severe ethical punishment, represents 66.67% of the penalties applied to accountants. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-069